2016
DOI: 10.1039/c5nj03354c
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring thermo-reversible dehydration of the pluronic microenvironment using 4-chloro-1-naphthol as an ESPT fluorescent molecular probe

Abstract: An ESPT fluorescent molecular probe, 4-chloro-1-naphthol, has been employed to study the thermo-reversible sol–gel transition, dehydration and micro-polarity of pluronics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…10 Roy et al have studied the efficiency of fluorescence resonance energy transfer between coumarin 153 and rhodamine 6G in pluronic f127 medium. 11 Sarkar has monitored the thermo-reversible dehydration of pluronic microenvironment using 4-chloro-1-naphthol as a fluorescent molecular probe 12 Khateb et al have reported the ocular drug delivery application of pluronic F127 along with pluronic F68. 13 Devi et al have developed the drug delivery and gene therapy utility of different poloxamers.…”
mentioning
confidence: 99%
“…10 Roy et al have studied the efficiency of fluorescence resonance energy transfer between coumarin 153 and rhodamine 6G in pluronic f127 medium. 11 Sarkar has monitored the thermo-reversible dehydration of pluronic microenvironment using 4-chloro-1-naphthol as a fluorescent molecular probe 12 Khateb et al have reported the ocular drug delivery application of pluronic F127 along with pluronic F68. 13 Devi et al have developed the drug delivery and gene therapy utility of different poloxamers.…”
mentioning
confidence: 99%
“…It is nontoxic, nonionic and amphiphilic . It is a thermoreversible gel having transition temperature of 20–22 °C . The process of gelation is both concentration and temperature dependent .…”
Section: Introductionmentioning
confidence: 99%